Cancer stem cells: An overview of the pathophysiological and prognostic roles in colorectal cancer. (April 2022) - Pashirzad, Mehran; Sathyapalan, Thozhukat; Sheikh, Afsana; Kesharwani, Prashant; Sahebkar, Amirhossein
Abstract: Colorectal cancer (CRC) is one of the most common types of cancer globally. A subpopulation of tumour cells, cancer stem cells (CSC), is speculated to be responsible for tumor initiation, development, maintenance, metastasis, and recurrence. Colorectal cancer stem cells (CRC-SCs) have demonstrated some unique features, including a high level of heterogeneity and plasticity. This review summarizes the current understanding of CRC-SCs in the progression of CRC and the prognostic importance of these CSCs and their markers in colorectal cancer. Moreover, we have also discussed about various therapeutic approaches against markers-expressing CRC-SC. Highlights: Colorectal cancer (CRC) is one of the most common types of cancer globally. Cancer stem cells (CSC) is responsible for tumor metastasis and recurrence. Colorectal cancer stem cells (CRC-SCs) have high level of heterogeneity and plasticity. We summarizes the current understanding of CRC-SCs in the progression of CRC.